Building a virtual factory: an integrated design approach to building smart factories. (23rd April 2021) - Yildiz, Emre; Møller, Charles
Abstract : Purpose: The complexity of manufacturing systems, on-going production and existing constraints on the shop floor remain among the main challenges for the analysis, design and development of the models in product, process and factory domains. The potential of different virtual factory (VF) tools and approaches to support simultaneous engineering for the design, and development of these domains has been addressed in the literature. To fulfil this potential, there is a need for an approach which integrates the product, process and production systems for designing and developing VF and its validation in real-life cases. This paper aims to present an integrated design approach for VF design and development, as well as a demonstration implemented in a wind turbine manufacturing plant. Design/methodology/approach: As the research calls for instrumental knowledge to discover the effects of intervention on the operations of an enterprise, design science research methodology is considered to be a well-suited methodology for exploring practical usefulness of a generic design to close the theory–practice gap. The study was planned as an exploratory research activity which encompassed the simultaneous design and development of artefacts and retrospective analysis of the design and implementation processes. The extended VF concept, architecture, a demonstration and procedures followed during the research work are presented and evaluated. Findings: The artefacts (models and methods) and the VF demonstrator, which was evaluated by industry experts and scholars based on the role of the VF in improving the performance in the evaluation and reconfiguration of new or existing factories, reduce the ramp-up and design times, supporting management decisions. Preliminary results are presented and discussed. Research limitations/implications: The concept VF model, its architecture and general methodology as an integrated design and development approach, can be adopted and used for VF design and development both for discrete and continuous manufacturing plants. The development and demonstration were limited, however, because real-time synchronisation, 3D laser scanning data and a commonly shared data model, to enable the integration of different VF tools, were not achievable. Originality/value: The paper presents a novel VF concept and architecture, which integrates product, process and production systems. Moreover, design and development methods of the concept and its demonstration for a wind turbine manufacturing plant are presented. The paper, therefore, contributes to the information systems and manufacturing engineering field by identifying a novel concept and approach to the effective design and development of a VF and its function in the analysis, design and development of manufacturing systems.